APPLICATION OF DIGITAL LITERACY PRACTICES IN THE INTRODUCTION OF LITERACY IN EARLY CHILDHOOD - Mulyati, Mulyati; Maesyaroh, Siti (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
The purpose of this study is to explore the practice of digital literacy in the introduction of literacy in early childhood. The research methodology used is descriptive qualitative, with literature review techniques sourced from previous journals according to the research topic in the last seven years, 2015-2022, and as many as 20 journals. The findings show that digital literacy has practically been applied in the early childhood learning environment. Digital-based children's learning media are increasingly varied, generally audio-visual, such as Android-based media and game applications to introduce children's literacy learning. The results of this study can be used as information in supporting the early childhood learning environment through the supporting role of parents, teachers, digital-based facilities, and infrastructure to help preschool children advance in spelling skills.